THE IMPACT ON THE DEVELOPMENT OF THE TAPPED FURNITURE ON THE DESIGN AND THE MATERIALS OF THE MODERN FURNITURE - Namicev, Petar; Doneva, Tatjana (Journal of process management and new technologies, 2019)
The design of furniture in the Middle Ages as a work of art made by top artists creates a great application in the development of a growing number of small pieces of furniture. The design of 15th-century stools, which was governed by nature, and the need for durable, simple and functional shapes, are also today widely used. Today, more homes use upholstery as a kind of decoration and durability. Today's modern furniture, such as furniture design from the 20th century, carries certain features, with simpler shapes and a richer selection of materials and with much simpler decoration. Based on the detailed analysis of the characteristics, as well as their comparison, we can see the connection between them.